Copeptin as a Biomarker of Microcirculation Alterations in Systemic Sclerosis - Maciejewska M; Stec A; Zaremba M; Maciejewski C; Rudnicka L; Sikora M (Dove Medical Press, 2023)
Magdalena Maciejewska,1 Albert Stec,2 Michał Zaremba,2 Cezary Maciejewski,3 Lidia Rudnicka,2 Mariusz Sikora4 1Department of Dermatology, Doctoral School of Medical University of Warsaw, Warsaw, Poland; 2Department of Dermatology, Medical University of Warsaw, Warsaw, Poland; 3 1st Department of Cardiology, Medical University of Warsaw, Warsaw, Poland; 4National Institute of Geriatrics, Rheumatology and Rehabilitation, Warsaw, PolandCorrespondence: Mariusz Sikora, National Institute of Geriatrics, Rheumatology and Rehabilitation, Spartańska 1, Warsaw, 02-637, Poland, Email drmariuszsikora@gmail.comBackground: Systemic sclerosis is a connective tissue disease characterized by vasculopathy and progressive fibrosis, leading to multiorgan dysfunction. Given the complex and not fully elucidated pathogenesis, biomarkers of rapid disease progression and therapeutic response are lacking. Copeptin, which reflects vasopressin activity in serum, is used in diagnosing or prognosing different cardiometabolic conditions.Objective: The aim of study was to investigate the concentration of copeptin in patients with systemic sclerosis and correlate it with specific clinical symptoms.Patients and Methods: Serum copeptin was measured in patients with systemic sclerosis (34 women and 3 men; mean age 57.6 years) and in healthy individuals (n=30) using commercially available ELISA kits. According to the criteria of LeRoy our systemic sclerosis cohort consisted of 17 patients with limited cutaneous systemic sclerosis (45.9%) and 20 diffuse cutaneous systemic sclerosis patients (54.1%). According to the criteria of LeRoy our systemic sclerosis cohort consisted of 17 patients with limited cutaneous systemic sclerosis (45.9%) and 20 diffuse cutaneous systemic sclerosis patients (54.1%). The median duration of the disease was 10 [4- 14] years.Results: We found significantly higher copeptin concentration in patients with systemic sclerosis (4.21 pmol/L [3.04- 5.42]) in comparison to control group (3.40 pmol/L [2.38- 3.76], p< 0.01). Copeptin significantly correlated with Raynaud's condition score (r=0.801, p< 0.05). Patients with "late" capillaroscopic patterns had higher copeptin concentrations (5.37 pmol/L [4.29- 8.06]) than patients with "early" (2.43 pmol/L [2.25- 3.20], p< 0.05) and "active" patterns (3.93 pmol/L [2.92- 5.16], p< 0.05]). Copeptin was found to be significantly higher in SSc patients with DUs (5.71 pmol/L [IQR 4.85- 8.06]) when compared to SSc patients without DUs (3.31 pmol/L, [2.28- 4.30], p< 0.05). Additionally, copeptin concentration had good diagnostic accuracy in discriminating between patients with and without digital ulcers (AUC=0.863). Alprostadil decreased copeptin concentration from 4.96 [4.02- 6.01] to 3.86 pmol/L [3.17- 4.63] (p< 0.01) after 4- 6 cycles of administration.Conclusion: Our findings suggest that copeptin may be a promising biomarker of microcirculation alterations in systemic sclerosis.Keywords: serum biomarkers, vasculopathy, endothelial dysfunction, digital ulcers, systemic sclerosis